Neurophysiological parameters of sensory perception and cognition among different modalities of learners - Rachna Parashar; Mukesh Shukla; Abhimanyu Ganguly; Sandip M Hulke (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Different types of learners based on sensory modalities are observed. Cognition or physiological alterations in the sensory pathways might play its role in different modalities of visual, auditory, read and write, and kinesthetic learners which are based on different sensory modalities of perception OBJECTIVE: The objective of this study is to ascertain an objective parameter (neurophysiological parameters) for the classification of learners based on their preferred sensory modality MATERIALS AND METHODS: An experimental cross-sectional study was conducted among 100 medical students. Learners were classified into visual, auditory, read-write, and kinesthetic learners based on the interpretation drawn on the basis of the VARK questionnaire. Sensory-evoked potentials (SEPs), including pattern shift visual (PSVEPs), brain stem auditory (BAEPs), short-latency somatosensory (SSEP), and event-related potentials (P300) were measured. SEPs measured in microvolts were recorded from the scalp with the help of active and reference electrodes. Multiple responses to sensory stimuli (using NIHON KOHDEN Corporation Neuropack X1, Tokyo, Japan) were recored and averaged using the computerized signal averging technique. RESULTS: No statistically significant difference was observed in conduction velocities (in terms of latency and amplitude) of SEP among different type of learners, except latency N145 wave form in VEP (P < 0.05). A characteristic pattern of minimal comparative latency was observed among the majority of visual learners. Similary, P300 has shown a characteristic pattern of decreased comparative latency among majority of read and write learners. CONCLUSION: Study findings suggested that among existing teaching and learning modalities, visual modalities were observed faster but to retain it in memory and for abstract thinking, students should utilize read and writing skills which are lacking in the era of digitalization and overuse of electronic devices.